Aportes Antropológicos para la inclusión laboral de las personas con necesidades especiales - Pico Arregui, Iris de las Mercedes (2014)
This work has a historical view of disability in society and their different conceptions, which we realize the social process from the absolute discrimination, to the personal recognition of the need to have a voice to claim their human rights away from the conception of disease that until last century was handled. There is an approach to the reality of work globally in which the barriers to employment is evident, given the technological transformation of labor, whereby the safe operation is an urgent need for the economic reality of our peoples. There is evidence that labor inclusion is a viable approach to improving living conditions, but the work is not summed to get the monthly salary, but the recognition of the ability that makes them part of society and productivity. Condition that is not yet recognized, especially in cases of intellectual and sensory disabilities.